Real ant colony optimization as a tool for multi-criteria problems - Nowak, Iwona; Nowak, Grzegorz (Computer Assisted Methods in Engineering and Science, 2015)
This paper presents a population-based heuristic method - a real ant colony optimization (RACO) as a tool for multi-criteria optimization problems. The idea of multi-criteria optimization is discussed and the necessary modifications of RACO are proposed. These modifications made possible to use the method to simultaneously search many Pareto-optimal solutions. The method was numerically tested in problems of benchmark-type and used for solving simple engineering problems. This article presents and discusses all results obtained in tests, and two different approaches to multi-criteria optimization are additionally compared (search then decision and decision then search).